2010
DOI: 10.1111/j.1460-9568.2010.07074.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced paternal age is associated with alterations in discrete behavioural domains and cortical neuroanatomy of C57BL/6J mice

Abstract: Advanced paternal age (APA) is associated with an increased risk of neurodevelopmental disorders such as autism and schizophrenia. A previous study in mice suggested that the offspring of aged sires have altered locomotion and avoidance learning. The aim of the current study was to conduct a comprehensive behavioural screen in adult offspring of mice of APA. We also examined brain morphology in neonate and adult mice. The adult offspring of 12- to 18-month-old (APA) and 4-month-old (control) male C57BL/6J mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 65 publications
5
46
1
Order By: Relevance
“…De novo germline mutations, epigenetic alterations and life course toxic exposure may partly explain the observed association. The evidence is substantial enough to justify a search for the underlying mechanisms in both human and animal models (55,56). …”
Section: Discussionmentioning
confidence: 99%
“…De novo germline mutations, epigenetic alterations and life course toxic exposure may partly explain the observed association. The evidence is substantial enough to justify a search for the underlying mechanisms in both human and animal models (55,56). …”
Section: Discussionmentioning
confidence: 99%
“…Another study comparably showed reduced capacity for passive-avoidance learning for offspring of older sires[41] and another found alterations in cortical growth, which are perhaps relevant to the behavioral findings[42]. Both schizophrenia and autism entail reduced learning ability, so these findings may be relevant to the mechanism linking later paternal age to these conditions[35, 43-45].…”
Section: Learning and Intelligencementioning
confidence: 99%
“…The ROI-based manual outlining of individual brain structures enables the estimation of absolute volumes but requires well-reasoned and time-consuming area demarcation, and the outlining protocols may not be compatible between different laboratories (Foldi et al, 2010;Hasegawa et al, 2010;Henke et al, 2008;Nagel et al, 2004;Sawiak et al, 2009a;Schubert et al, 2008Schubert et al, , 2009. Unfortunately, manual approaches fail if the volumes of selected structures differ partially by small amounts.…”
Section: Introductionmentioning
confidence: 98%